Beyond Digital Knowledge: The Dominant Roles of User Vigilance and Two-Factor Authentication in E-Commerce Phishing Susceptibility - Siti Syahara; Juli Dwina Puspita Sari; Shelly Midesia (FEBI IAIN Langsa, 2026)
While e-commerce growth accelerates digital adoption, phishing remains a critical threat to transaction trust. Previous research frequently conflates passive literacy with active defensive habits, leaving a gap in understanding how cognitive, behavioral, and technical safeguards distinctly mitigate threat exposure within emerging regional markets. This study evaluates the impact of Digital Security Knowledge (X1), User Awareness (X2), and Two-Factor Authentication (2FA) usage (X3) on Phishing Vulnerability (Y) among e-commerce consumers in Langsa City, Indonesia. Utilizing a quantitative survey design (n=100) and multiple linear regression analysis, the empirical model accounted for 78.3% of the variance in phishing vulnerability (Adjusted R2 = 0.783, F = 116.452, p < 0.001). The structural model reveals a distinct behavioral hierarchy: while all three variables share a significant inverse relationship with vulnerability, technical and active safeguards are overwhelmingly dominant. Utilizing 2FA emerged as the most dominant predictor in neutralizing credential exploitation (t = -6.241, p < 0.001), followed closely by real-time User Awareness (t = -6.092, p < 0.001), whereas conceptual Digital Security Knowledge exerted a remarkably weak effect (t = -2.184, p = 0.031). This reveals that passive knowledge fails under transactional pressure without hard technical barriers and active cognitive skepticism. From an Islamic economic perspective, safeguarding wealth (Hifdz al-Mal) against digital fraud (gharar) requires operationalized ikhtiyar (purposeful effort). Practically, e-commerce platforms must enforce mandatory default 2FA, while public initiatives should pivot toward scenario-based active awareness training to secure the digital muamalah ecosystem.